رؤى في تخطيط ورش العمل في مجال إدارة الكوارث (Journal of Faculty of Education, 2021)
This article aims at providing workshops' planning skills for those concerned with training in the field of disaster management, besides assisting junior trainers in this same field to develop their abilities and rub up on their experiences for better training performance. The article is not more than aggregation of the author’s personal experience in disaster management training courses and workshops delivered by him to government authorities and nongovernmental organizations staff for more than ten years. General introduction, training related concepts and definitions, importance of training, and training and teaching relation were tackled. Special emphasis was given to workshops planning in disaster management through: training needs; objectives; materials; programme; implementation; and evaluation. The article shows that planning for disaster management workshops requires a highly skilled trainer who is well aware of three dimensions: (i) Education: that is to: design workshop materials, determine the appropriate teaching method and evaluate workshop activities. (ii) Administration: that is to: explain management concepts, functions, planning, organization, decision making, leadership, follow up, and human and financial management. (iii) Knowledge: to be knowledgeable in disaster management, (mitigation, preparation, response, and recovery). Planning and implementation of disaster management workshops, based on these dimensions, will defiantly guarantee a successful workshop, however, this success is conditioned by the trainer’s follow up to recent scientific research results in disaster management, and recent training methods, because training is a continuous process.
Keywords: إدارة الكوارث; المنظمات الطوعية